2007
DOI: 10.1016/j.yjmcc.2006.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine A attenuates mitochondrial permeability transition and improves mitochondrial respiratory function in cardiomyocytes isolated from dogs with heart failure

Abstract: Objective-We used isolated cardiomyocytes to investigate a possible role of mitochondrial permeability transition pore in mitochondrial abnormalities associated with heart failure.Methods-Cardiomyocytes were isolated from LV myocardium of normal control dogs and dogs with heart failure produced by intracoronary microembolizations. Mitochondrial permeability transition was measured in isolated cardiomyocytes with intact sarcolemma with and without 0.2 μM Cyclosporin A using calcein AM and the fluorometer. State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 43 publications
4
77
0
1
Order By: Relevance
“…These two phenomena are both delayed by cyclosporine A, indicating that they are due to mPTP opening, and suggest that they correspond to the transient (reversible) and long-lasting openings (irreversible) of the pore as described previously (Hü ser and Blatter, 1999;Sharov et al, 2007). Our study reveals for the first time that morphine and SB are as efficient as cyclosporine A in preventing mPTP opening.…”
Section: Discussionsupporting
confidence: 86%
“…These two phenomena are both delayed by cyclosporine A, indicating that they are due to mPTP opening, and suggest that they correspond to the transient (reversible) and long-lasting openings (irreversible) of the pore as described previously (Hü ser and Blatter, 1999;Sharov et al, 2007). Our study reveals for the first time that morphine and SB are as efficient as cyclosporine A in preventing mPTP opening.…”
Section: Discussionsupporting
confidence: 86%
“…Two types of fluorescent signal kinetics were observed: either a gradual decrease or a complete and rapid drop in calcein fluorescence. These phenomena probably correspond to the transient (reversible) and long-lasting (irreversible) opening of the mPTP as described previously (Sharov et al, 2007). TRO40303 greatly increased the percentage of cardiomyocytes that displayed gradual mPTP openings compared with that in control cells (Table 1).…”
Section: Tro40303 a Newsupporting
confidence: 78%
“…Indeed, MPTP opening has been demonstrated in HF induced by myocardial infarction in rats (Javadov et al, 2005) and intracoronary microembolizations in dogs (Sharov et al, 2007), as well as in Ca 2ϩ -induced cardiomyopathy (Nakayama et al, 2007) and diabetic cardiomyopathy (Oliveira et al, 2003). Notably, our studies have demonstrated that the extent of MPTP opening in failing hearts 12 and 18 weeks after coronary artery ligation (Javadov et al, 2005) is lower than that found following acute IR (Griffiths and Halestrap, 1995;Kerr et al, 1999;Javadov et al, 2003).…”
Section: Heart Failurementioning
confidence: 50%